Parathyroid Carcinoma: Update on Pathogenesis and Therapy - Francesca Marini; Francesca Giusti; Gaia Palmini; Cinzia Aurilia; Simone Donati; Maria Luisa Brandi (Endocrines, 2023)
Parathyroid carcinoma (PC) is a very rare endocrine cancer with aggressive behavior, a high metastatic potential, and a poor prognosis. Surgical resection of affected gland(s) and other involved structures is the elective therapy. Pre-operative and intra-operative differential diagnosis with benign parathyroid adenoma remains a challenge. The lack of a clear pre-operative diagnosis does not allow one, in many cases, to choose the correct surgical approach to malignant PC, increasing persistence, the recurrence rate, and the risk of metastases. An initial wrong diagnosis of parathyroid adenoma, with a minimally invasive parathyroidectomy, is associated with over 50% occurrence of metastases after surgery. Genetic testing could help in identifying patients at risk of congenital PC (i.e., CDC73 gene) and in driving the choice of neck surgery extension. Targeted effective treatments, other than surgery, for advanced and metastatic PC are needed. The pathogenesis of malignant parathyroid carcinogenesis is still largely unknown. In the last few years, advanced molecular techniques allowed researchers to identify various genetic abnormalities and epigenetic features characterizing PC, which could be crucial for selecting molecular targets and developing novel targeted therapeutic agents. We reviewed current findings in PC genetics, epigenetics, and proteomics and state-of-the-art therapies.